A study on the role of religion in the use of residential interior spaces among selected middle-class Filipino catholic families - Faustino, Johanna Victoria Acab; Mayo, Adelaida V. (2008.)
This study explored various manifestations of religiosity in the homes of selected urban Filipino middle class families. Home interior space use pertaining to usual locations for display of religious items was observed. An analysis of the meanings behind these manifestations was done. The study was qualitative in nature and used a descriptive design. Fifteen Filipino Catholic families were purposely chosen and further subdivided to three middle class levels: lower middle, middle-middle, and upper-middle income classes. Identification of social strata was based on the family income, type of community, materials used in the structure of home, interior finishes, accessories, size of the house and estimated price lots in the community. Data was collected through survey questionnaires, interviews, observation and photo documentation. The theory of proxemics (Hall) was used in studying the spatial organization and relationship of activities pertaining to Catholic and non-Catholic practices. The theory of semiotics was likewise utilized to establish meanings behind a particular space or object. Results showed that the practice of religion is generally private and personal, as evidenced by the highest quantity of religious items found in bedrooms. Semi-private spaces, such as hallways, staircases and anterooms were likewise the preferred locations of religious items. Living areas were used for communal prayers especially in the case of lower-middle families where space is limited, and also a venue to display cherished religious collections of some middle-middle and upper middle families. although prayer was often made at mealtimes, results indicated that semi-public areas would normally contain just an image of the Last Supper. Thresholds were also found to be one of the preferred locations of the display of religious items primarily meant for protection against evil spirits and events. The statue, among all types of religious items was still considered as the most important type of religious article for two possible reasons: (1) as an aid for prayer and (2) because of the sentimental value attached to it. Findings reinforce the notion that the Philippines is a Marian country since images of Mary appeared to be the most significant in number. All respondent Catholic families practiced at least one religious act in their home. However, non-Catholic beliefs and practices such as Feng Shui and the placement of items attracting wealth, luck, and protection were likewise evident in some families even to the point of integrating these practices to their religious faith. It was found that Cultural Catholicism has not totally eliminated animism from Filipino culture. Non-Catholic beliefs and practices may have tendency to be intertwined with Catholic beliefs and practices, which eventually affected the use of home interior spaces. Religion is a significant factor in the use of space of the respondent families. Therefore, designers and space planners should be aware that while the practice of religion is a personal matter, they are responsible in guiding their clientele about how they can integrate their religious practices, without sacrificing the utilitarian and aesthetic principles of design.
Thesis (M.I.D)--University of the Philippines Diliman.
Keywords: Interior architecture -- Philippines -- Religious aspects; Space (Architecture) -- Philippines -- Religious aspects